2021
DOI: 10.3390/land10050506
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Gu et al. Qualifying Land Use and Land Cover Dynamics and Their Impacts on Ecosystem Service in Central Himalaya Transboundary Landscape Based on Google Earth Engine. Land 2021, 10, 173

Abstract: In the original article [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In ESV coefficient, showed an increasing trend of ESV from 2010 to 2020 due to an increase in forest cover through the agriculture area decreases by 1.99%, which implies that ESV is mostly dependent upon the forest because it provides a wide variety and high-value ecosystem services. The other studies also revealed a decrease in ESV due to a decrease in forest cover (Sharma et al, 2019) (Gu et al, 2021).…”
Section: Results and Discussion Land Use Land Cover Change Analysismentioning
confidence: 88%
“…In ESV coefficient, showed an increasing trend of ESV from 2010 to 2020 due to an increase in forest cover through the agriculture area decreases by 1.99%, which implies that ESV is mostly dependent upon the forest because it provides a wide variety and high-value ecosystem services. The other studies also revealed a decrease in ESV due to a decrease in forest cover (Sharma et al, 2019) (Gu et al, 2021).…”
Section: Results and Discussion Land Use Land Cover Change Analysismentioning
confidence: 88%
“…The differential evolution algorithm (DEA) is an optimization algorithm used to find an optimal solution to a problem by simulating the biological evolution process . This method is based on the natural processes of natural selection and evolution.…”
Section: Methodsmentioning
confidence: 99%
“…Otherwise, go back to step 2 and continue until the stopping criterion is met. The stopping criterion is generally the maximum number of iterations and/or when the population objective function no longer changes Table shows the parameters used for the DEA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations